2019
DOI: 10.3892/ol.2019.10490
|View full text |Cite
|
Sign up to set email alerts
|

Maximum allele frequency observed in plasma: A potential indicator of liquid biopsy sensitivity

Abstract: Personalized medicine is revolutionizing the diagnosis and treatment of cancer; however, for personalized medicine to be used accurately, patient information is essential to determine the appropriate diagnosis, prognosis and treatment. The detection of genomic mutations in liquid biopsy samples is a non-invasive method of characterizing the genotype of a tumor. However, next generation sequencing-based plasma genotyping only has a sensitivity of ~70%. Identifying potential indicators that may reflect the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, it was not successful due to insufficient tissue in the supraclavicular lymph nodes. Interestingly, a prospective study observed only a 62.0% by variant concordance rate among primary tumor, metastatic lymph nodes, and plasma, suggesting that there is some deviation between the detection of plasma samples and the detection of primary tumor samples (5). Therefore, the genetic test results of the first blood sample do not reflect the actual mutation status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it was not successful due to insufficient tissue in the supraclavicular lymph nodes. Interestingly, a prospective study observed only a 62.0% by variant concordance rate among primary tumor, metastatic lymph nodes, and plasma, suggesting that there is some deviation between the detection of plasma samples and the detection of primary tumor samples (5). Therefore, the genetic test results of the first blood sample do not reflect the actual mutation status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from tTMB, the analysis of bTMB had been found to be impacted by several factors in the blood, including ctDNA, AF, MSAF grouping, ITH, etc. [ 13 , 20 , 21 , 22 , 23 , 24 ]. Considering that a patient with advanced NSCLC is characterized by high tumor burden and ITH, the relationship among bTMB, MSAF, and ITH has been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence data analysis was conducted with a bioinformatics pipeline as previously described 45 . The maximum allele frequency of somatic mutations in plasma was used to determine the changes of ctDNA 46 .…”
Section: Methodsmentioning
confidence: 99%